PENERAPAN MODEL PROBLEM BASED LEARNING TENTANG NILAI MUTLAK DI KELAS X SMA 9 PONTIANAK - Martanto, Rahmad; Jamiah, Yulis; Yani, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research aims to know and describe the effectiveness of Problem Based Learning model in the absolute value topic at class X of SMA Negeri 9 Pontianak Mathematic and Science Department. The aspects that want to be knowand describe are the implementation of the learning process, student’s learning activities, student’s respond and student’s outcomes. The research method is quantitative method. The research subject is students in class X MIA 2. Based on the data analysis from four aspects are: (1) the implementation of the learning process categorized very good with average score 3,64; (2) student’s learning activities categorized active (87,83%); (3) student’s respond categorized very positive with 28 student (82,35%) and 6 student (17,65%) give a positive respond; and (4) student’s outcome is reached classical completeness with 85,29% of student can achieve the minimum completeness criteria. Because four aspects achieved, the conclusion of this research is the implementation of Problem Based Learning model effective in the absolute value topic at class X MIA 2 SMA Negeri 9 Pontianak.. Keywords:  Problem Based Learning Model, Absolute Value Subject, Effectiveness